Tricyclic Antidepressants in Chronic Low Back Pain : A Review - Ilmanita, Dzikrina; Hidayati, Hanik Badriyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Chronic low back pain (LBP) is the frequent chronic pain and notable health problem which is the main reason of disabling conditions, individual suffering, sick leave, and costly treatment.Â Unfortunately, available therapy especially oral medicines only beneficial in no more than 50% of patients. Tricyclic antidepressants (TCAs) are commonly used for neuropathic pain but the data for neuropathic LBP is limited. The purpose of this review is to evaluate the efficacy and adverse drug reaction of TCAs in chronic LBP. We searched scientific search engines including Scopus and PubMed and collected original articles including Randomized Clinical Trial (RCT), comparative, and observational study about Tricyclic Antidepressants treatment in chronic LBP from 1998 to 2019. In this review, 5 articles and 543 patients were evaluated. All recruited articles are randomized clinical trials. Among all five relevant articles, three of them evaluate amitriptyline treatment in chronic LBP while the rest articles evaluate imipramine and nortriptyline. Amitriptyline is the most well-studied TCA for chronic LBP. We found that both amitriptyline and nortriptyline can reduce pain severity significantly when the dose is increased gradually depending on patient tolerance. TCAs can also improve disability significantly. However, single-dose imipramine is not superior than placebo. We conclude that TCAs can be effective for treating chronic LBP when used routinely for several weeks and the dose should be increased gradually depending on patient tolerance although further studies are required to confirm the optimal dose for analgesia. The most prevalence Adverse Drug Reactions (ADRs) of TCA including dry mouth, somnolence, insomnia, sedation, and constipation.